Ecumenical lessons of history - Kopiec, Piotr (Edinost in dialog, 2025)
From its outset, the ecumenical movement struggled with a problem of memories, particularly concerning collective memories of nations. The first ecumenical gatherings had to bridge the wounds of remembrance of people who belonged to different and often hostile nations. Nevertheless, this early experience had helped elaborate teaching that later became a theological ‘vaccine ’ for the following decades of ecumenical strivings. Ecumenism needs this vaccine, since existential and spiritual clashes of fidelity to Jesus’s call to unity and loyalty to national identity still happen. The article aims to showcase the work of two Polish ecumenists who advocated for Christian unity and, at the same time, for reconciliation between Poland and its neighbours during the communist epoch. An extensive outline of the ecumenical theory on nationalism, nation, relationships between nations and the Church, and reconciliation among nations precedes the presentation.
Keywords: ecumenism; ekumenizem; history; reconciliation; remembrance; spomin; sprava; zgodovina